The Dialectics of Free Energy Minimization - Boonstra, Evert A.; Slagter, Heleen A. (Frontiers in Systems Neuroscience, 2019)
Karl Friston’s free energy minimization has been received with great enthusiasm. With good reason: it not only makes the bold claim to a unifying theory of the brain, but it is presented as an a priori principle applicable to living systems in general. In this paper, we set out to show how the breadth of scope of Friston’s framework converges with the dialectics of Georg Hegel. Through an appeal to the work of Catherine Malabou, we aim to demonstrate how Friston not only reinvigorates Hegelian dialectics from the perspective of neuroscience, but that the implicit alignment with Hegel necessitates a reading of free energy minimization from the perspective of Hegel’s speculative philosophy. It is this reading that moves beyond the discussion between cognitivism and enactivism surrounding Friston’s framework; beyond the question whether the organism is a secluded entity separated from its surroundings, or whether it is a dynamical system characterized by perpetual openness and mutual exchange. From a Hegelian perspective, it is the tension between both positions itself that is operative at the level of the organism; as a contradiction the organism sustains over the course of its life. Not only does the organism’s secluded existence depend on a perpetual relation with its surroundings, but the condition for there to be such a relation is the existence of a secluded entity. We intend to show how this contradiction – tension internalized – is at the center of Friston’s anticipatory organism; how it is this contradiction that grounds the perpetual process of free energy minimization.